PERAN MEDIASI OCB PADA PENGARUH THE BIGJFIVE PERSONALITY TERHADAP KINERJA PERAWAT RSUD DR. SOEDIRMAN KEBUMEN - Anton Prasetyo (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2022)
Organizational Citizenship Behavior (OCB) has an important role in organizational effectiveness because basically OCB attitudes can improve organizational performance. This study aims to determine and test the bigative personality effect on performance with OCB as a mediating variable in nurses at RSUD dr. Soedirman Kebumen. This study uses a quantitative approach. The data used is primary data in the form of questionnaire answers from 155 respondents. The analysis tool uses the Partial Least Square Structural Equation Model (PLS-SEM) analysis. The results of the analysis show that the big five personality dimensions, namely extraversion, acceptance, conscientiousness, oneuroticism and openness to experience have a positive and significant effect on OCB; the dimensions of extraversion, conscientiousness and openness to experience have a positive and significant effect on performance, while the dimensions of agreeableness and neuroticism have no effect on performance; OCB has a positive and significant influence on performance; and OCB were able to mediate the effect of agreeableness, conscientiousness, and openness to experience on performance, and OCB could not mediate the effect of extraversion and neuroticism on performance.